1996
DOI: 10.1097/00007632-199601010-00018
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Disc High-intensity Zone

Abstract: In patients with symptomatic low back pain, the high-intensity zone is a reliable marker of painful outer anular disruption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(40 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…Similar clinical studies followed [57]. Chen et al [6] reported a correlation between the HIZ and positive concordant pain on discography, and Peng et al [8] and Dongfeng et al [9] found inflammation and neovascularization on histological analysis of disc material in the HIZ.…”
Section: Introductionmentioning
confidence: 57%
“…Similar clinical studies followed [57]. Chen et al [6] reported a correlation between the HIZ and positive concordant pain on discography, and Peng et al [8] and Dongfeng et al [9] found inflammation and neovascularization on histological analysis of disc material in the HIZ.…”
Section: Introductionmentioning
confidence: 57%
“…The findings of disc desiccation and the presence of a high-intensity zone have been shown to have a high correlation with an annular tear in most patients (25,26) (Fig. 4).…”
Section: Indications Idetmentioning
confidence: 87%
“…Carragee et al [31] highlighted the issue of iatrogenic degenerative changes from testing "healthy" control discs required for concordant testing, and drew attention to the significant influence of psychosocial overlay and secondary gains in false positive results. However, confusion still exists, with high sensitivity and specificity [32], high likelihood ratios [3334] and low false positive rates found in selected studies [35] which may be related to the technique using a pain-free control disc and volume related pressure [36]. …”
Section: Imagingmentioning
confidence: 99%